Die Niederschlagsjahreszeiten in Ecuador und ihre klimadynamische Interpretation - Bendix, Jörg; Lauer, Wilhelm (ERDKUNDE, 1992)
In Ecuador the solar determination of annual rainfall variation is conspicuously modified by the influence of the Andean mountain system, the competitive ocean currents (Nino- and Humboldt-Current), as well as the mesoscale phenomenon of the valley winds. By means of a factor analysis, four main-and two transitional types of precipitation regimes can be distinguished. Due to the influence of the earth´s surface, the normal equatorial type of the southern hemisphere is just revealed in the highlands. The coastal area and the lowlands of the eastern Andean slope have different types with a single precipitation maximum during summer and well defined wintry dry seasons (July) at the coast, and a regime with three peaks and precipitation over all season in the Amazon Lowlands. A special type with a single rainfall maximum in Winter (July), without a real dry season over the year, occurs in the range of the eastern Andean slope at heights between 1000 to 3500 m a.s.l. A correlation analysis between the annual variation of rainfall and the wind direction, as well as the frequency of thunderstorms, provides explanations for the occurence of the different precipitation regimes. The interpretation of satellite images connects the results with the global system of circulation and weather over north-western South America.